The use of multi-sensor for illegal human settlement detection / Arnis Asmat, S.Z. Zamzami and S. Mansor - Zamzami, S.Z; Mansor, S. (Faculty of Architecture, Planning and Surveying, 2012)
The paper presents preliminary results of legal and illegal settlement extraction in Pulau Gaya, Sabah using high resolution Quickbird and SPOT- 5 multi-spectral imageries using automated house detection technique. The technique developed is spatial-based using tree counting approach. From the results, edge to edge of the house features was found precisely separated and can be delineated between houses that less than 2m distance. Results show that the technique able to delineate legal houses from Quickbird image more than SPOT-5. Differs results would be due to different spatial and spectral resolution of images.